MOTIVASI DAN LINGKUNGAN KERJA SERTA PENGARUHNYA TERHADAP KINERJA KARYAWAN PT X DI KOTA MALANG - Krisdianto, Dadang; Widiastuti, Tri Marhaeni (JOURNAL AKSES STIA MALANG, 2024)
This research aims to analyze the influence of motivation and work environment on employee performance, both partially and jointly. In the context of globalization and increasingly tight business competition, employee performance has become an important factor that determines organizational success. Motivation and work environment have been proven to have a significant effect on individual performance. This research uses a survey method with a quantitative approach. The research population was employees of PT X in Malang, with a sample of 100 people selected purposively. The research instrument is a closed questionnaire with a Likert scale that measures work motivation, work environment and employee performance. Data were analyzed using descriptive analysis, correlation tests and regression. The research results show that work motivation and work environment have a positive and significant influence on employee performance. The correlation test shows a positive relationship between motivation and employee performance (r = 0.65, p < 0.01), as well as between the work environment and employee performance (r = 0.60, p < 0.01). The regression test shows that motivation (β = 0.50, p < 0.01) and work environment(β = 0.45, p < 0.01) together explain 70% of employee performance variability (R² = 0.70). This research emphasizes the importance of motivation and work environment in improving employee performance. Therefore, management must consider these two factors simultaneously in its human resource development strategy to achieve optimal productivity and job satisfaction.